2016
DOI: 10.12659/msm.897297
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes and Complications in Treatment of Terrible Triad of the Elbow: Comparisons of 3 Surgical Approaches

Abstract: BackgroundThis study compared the efficacy of combined lateral and medial approach, lateral approach, and anterior medial approach in treatment of terrible triad of the elbow (TTE).Material/MethodsThirty-eight TTE patients hospitalized in our center were retrospectively analyzed, among which 14 patients were arranged for combined lateral and medial approach, 12 for lateral approach, and 12 for anterior medial approach. All included patients underwent open reduction, collateral ligament repair, and postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…This is expected since combined approach led to more extensive dissection as compared to lateral approach and is much more complicated surgical procedure. Chen demonstrated an increased healing time with combined approach when compared to lateral approach [6]. The increased healing time in turn may lead to delayed recovery.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is expected since combined approach led to more extensive dissection as compared to lateral approach and is much more complicated surgical procedure. Chen demonstrated an increased healing time with combined approach when compared to lateral approach [6]. The increased healing time in turn may lead to delayed recovery.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is still no consensus on the better approach. Chen et al, [6] demonstrated that combined approach leads to extended surgical exposure, fracture stability and reduced complication rate compared to lateral approach. To facilitate a clinical decision, we conducted a meta-analysis comparing lateral approach and combined approach for terrible triad of elbow We found that the elbow range of motion, pronationsupination and MEPS were significantly more in the combined approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional posterior trans‐olecranon approach requires an extended posterior incision, extensive free medial and lateral skin flaps, and removal of the olecranon, which may result in serious damage to the soft tissue, a compromised blood supply, new fractures, and elbow stiffness. Researchers have noted that the CLMA achieves a better therapeutic effect than the single lateral approach or single anteromedial approach for TTI 14 . The CLMA may be the preferred choices for the treatment of TTI.…”
Section: Introductionmentioning
confidence: 99%
“…Elle est indiquée pour les patients présentant une instabilité résiduelle après réparation des lésions latérales. Il existe toutefois peu de séries homogènes évaluant les résultats cliniques à long terme de ces réparations médiales(12,14,15). L'objectif principal de cette étude était d'évaluer les résultats cliniques du traitement chirurgical des TTC.…”
unclassified